2018
DOI: 10.1111/nuf.12280
|View full text |Cite
|
Sign up to set email alerts
|

Medical assistance in dying (MAiD): Canadian nurses’ experiences

Abstract: Medical assistance in dying (MAiD) represents a historic change in Canadian society and the provision of end‐of‐life care. In this descriptive narrative inquiry, 17 nurses were interviewed during the first 6 months of assisted dying becoming a legal option for patients in Canada. Nurses’ experiences of either providing care for a patient who had chosen MAiD, or declining to participate in MAiD, were explored. Findings describe three themes and eight storylines of the impact of MAiD on nurses’ view of the profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(168 citation statements)
references
References 18 publications
2
163
0
3
Order By: Relevance
“…Such difficulties were further highlighted in a recent descriptive narrative inquiry by Beuthin et al (). In this study, 17 nurses were interviewed about their experience of MAiD.…”
Section: Political Ramifications and Professional Tensionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Such difficulties were further highlighted in a recent descriptive narrative inquiry by Beuthin et al (). In this study, 17 nurses were interviewed about their experience of MAiD.…”
Section: Political Ramifications and Professional Tensionsmentioning
confidence: 98%
“…Similar to countries such as Belgium and Switzerland, and to certain states within the United States of America, Canada has undergone legal transitions that support new end‐of‐life options for patients (Beuthin, Bruce, & Scaia, ). In 2015, physician‐assisted suicide was legalized in Canada through the Carter v. Canada (Attorney General) decision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, preliminary evidence from nurses in Canada suggests that this process is a bit more complicated than it might initially appear. Nurses may not necessarily be confident in their initial moral positioning but rather need to work it out over time (Beuthin, Bruce, & Scaia, ). This shouldn't surprise us when we realize that much of the willingness to participate in MAiD is related to family and peer influences (Lavoie et al, ) and, as society becomes more familiar with MAiD and the views of such influencers evolve, nurses’ moral comfort with the act may evolve over time as well.…”
Section: Nurses’ Legal and Ethical Obligations Regarding Maid: A Convmentioning
confidence: 99%
“…A descriptive narrative study of 17 nurses across Vancouver Island providing care for a patient who had chosen MAID or declined to participate in the first 6 months following legalization found that most participants saw MAID as an extension of the profession and nursing practice. However, while there is some discussion regarding siting and starting intravenous infusions, it is not clear how directly involved in MAID the nurses were (Beuthin, Bruce, & Scaia, ). While it is still too early to assess the full impact of MAID on nursing practice, the Canadian Nurses Association has provided guidance and recognizes that “ nurses have a unique perspective and bring an important contribution to the healthcare team in the provision of palliative and end‐of‐life care that includes MAID” (Canadian Nurses Association, p 24).…”
Section: Implications For Nursing Practicementioning
confidence: 99%